The Structuralist Perspective on Real Exchange Rate, Share Price Level and Employment Path: What Room Is Left for Money? - Phelps, Edmund S. (Institutional Knowledge at Singapore Management University, 2004)
The current sluggish performance of the US economy follows one of the more remarkable booms in modern history. The late 1990s was a period of simultaneous output and productivity growth,1 low unemployment and stable inflation, culminating in an unemployment rate of only 3.9% in the fourth quarter of the year 2000. The absence of rising inflation during this period came as a surprise to many since the level of the natural rate of unemployment was commonly estimated to be in the range of 5-6% by the mid 1990s. The non-inflationary boom, however, reminds one of another episode where non-monetary forces were strongly at work, namely, the non-deflationary slump in Europe and elsewhere in the 1980s and 90s, which appeared to signal a move to a higher natural rate of unemployment. The modeling of such structural slumps and booms is the task that we have tackled in a number of papers in recent years, the book Structural Slumps being a major milestone.